The Impact of Digital Literacy on STEM Competencies among High School Students - Reni Kurnia; Fitrika Kumala Dewi; Nizwardi Jalinus; Rijal Abdullah; Ridwan Ridwan (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2026)
This study analyses the influence of digital literacy on the STEM (Science, Technology, Engineering, and Mathematics) competencies of high school students. Digital literacy is one of the key 21st-century competencies that plays a role in helping students access, evaluate, and utilize digital information to support STEM learning. The study employed a quantitative approach using a survey design that involved 133 high school students as respondents. Data were collected using digital literacy and STEM competency questionnaires that met validity and reliability criteria. Data analysis was conducted using descriptive statistics, Pearson’s correlation, and linear regression. The results indicate that students’ digital literacy levels fall into the high category (M = 3.968; ? = 0.890), and their STEM competencies also fall into the high category (M = 3.618; ? = 0.899). Correlation analysis showed a positive and significant relationship between digital literacy and STEM competencies (r = 0.661; p < 0.001). Regression results indicate that digital literacy has a positive and significant effect on STEM competencies (? = 0.694; t = 10.078; p < 0.001), contributing 43.7% (R² = 0.437). These findings suggest that strengthening the digital literacy can be an effective strategy for improving students’ STEM competencies and supporting their readiness to face 21st-century challenges.